2017
DOI: 10.1088/1361-6528/aa9b18
|View full text |Cite
|
Sign up to set email alerts
|

Substrate effects in high gain, low operating voltage SnSe2photoconductor

Abstract: High gain photoconductive devices find wide spread applications in low intensity light detection. Ultra-thin layered materials have recently drawn a lot of attention from researchers in this regard. However, in general, a large operating voltage is required to obtain large responsivity in these devices. In addition, the characteristics are often confounded by substrate induced trap effects. Here we report multi-layer SnSe based photoconductive devices using two different structures: (1) SiO substrate supported… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…This is in agreement with our previous KPFM measurements which show that the SnSe2 is degenerately n-doped with the Fermi level about 0.3 eV above conduction band (CB) minimum. 40 The screening offered by the large carrier concentration suppresses strongly bound exciton state in SnSe2. Throughout this paper, we thus assume that the transition dipole in SnSe2 is governed by free electron-hole pairs.…”
Section: Evidence Of Fret Mechanismmentioning
confidence: 99%
“…This is in agreement with our previous KPFM measurements which show that the SnSe2 is degenerately n-doped with the Fermi level about 0.3 eV above conduction band (CB) minimum. 40 The screening offered by the large carrier concentration suppresses strongly bound exciton state in SnSe2. Throughout this paper, we thus assume that the transition dipole in SnSe2 is governed by free electron-hole pairs.…”
Section: Evidence Of Fret Mechanismmentioning
confidence: 99%
“…183 Raman spectroscopy has been shown to be a feasible tool to define the thickness of SnSe 2 , in which the difference between the two Raman peaks, namely E g and A 1g (located at B110 and B188 cm À1 , respectively), increases as the thickness decreases. 184 The photoresponse range of SnSe 2 can extend to the IR range. Using thick films, Mukhokosi et al demonstrated SnSe 2 photodetectors with R as high as B2 mA W À1 to 1064 nm light.…”
Section: Main Group Metal Chalcogenidesmentioning
confidence: 99%
“…To further validate this method, we fabricated a separate TaSe 2 -WS 2 -SnSe 2 stack where SnSe 2 is a degenerately n-doped, highly conductive layered semiconductor. 21 The extracted SBH value of SnSe 2 is 0.71 eV (See Supporting Figure S4), which corresponds to S = 0.8, indicating a highly de-pinned contact.…”
Section: Sources Of Ambiguity In Sbh Extractionmentioning
confidence: 99%